2015
DOI: 10.1371/journal.pone.0128016
|View full text |Cite
|
Sign up to set email alerts
|

Capsiate Supplementation Reduces Oxidative Cost of Contraction in Exercising Mouse Skeletal Muscle In Vivo

Abstract: Chronic administration of capsiate is known to accelerate whole-body basal energy metabolism, but the consequences in exercising skeletal muscle remain very poorly documented. In order to clarify this issue, the effect of 2-week daily administration of either vehicle (control) or purified capsiate (at 10- or 100-mg/kg body weight) on skeletal muscle function and energetics were investigated throughout a multidisciplinary approach combining in vivo and in vitro measurements in mice. Mechanical performance and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…Another possible interpretation is that the capsinoids were responsible for the change in energy production. Both one-time ingestion and 2 week continuous ingestion of capsinoids suppressed glucose use by increasing oxidative phosphorylation in muscles and facilitating lipid use [42,43]. Additionally, mice that ingested capsinoids exhibited longer endurance swimming capacity, implying that capsinoids-induced change in energy production increases endurance exercise capacity [44].…”
Section: Discussionmentioning
confidence: 99%
“…Another possible interpretation is that the capsinoids were responsible for the change in energy production. Both one-time ingestion and 2 week continuous ingestion of capsinoids suppressed glucose use by increasing oxidative phosphorylation in muscles and facilitating lipid use [42,43]. Additionally, mice that ingested capsinoids exhibited longer endurance swimming capacity, implying that capsinoids-induced change in energy production increases endurance exercise capacity [44].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports showed that the plasma glucose of CAP-treated rats at a dose of 15 mg/kg was significantly higher than the non-CAP-treated control group after immediate exhaustion [37]. The other studies also demonstrated that CAP increased glucose uptake directly by activating AMP-activated protein kinase (AMPK) [38], improved oxidative metabolism in exercising muscle, and promoted muscular mass gain with chronic administration [39]. Therefore, continuous 4 weeks CAP supplementation could increase energy utilization and improve exercise performance in current results (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…Interference with the function of these organelles is an important factor in developing insulin resistance in skeletal muscle [ 170 ]. Capsiate has shown beneficial responses in skeletal muscle function [ 171 , 172 ]; thus, capsaicin or its analogues can be targeted for improving skeletal muscle function. Similarly, mitochondrial function in liver was improved by a combination of capsaicin and α-tocopherol [ 79 ], further suggesting potential in targeting mitochondrial function with capsaicin.…”
Section: Capsaicin As a Treatment For Metabolic Syndromementioning
confidence: 99%